(untitled) (Web of Teachers: Inderscience Research, 2026)
The article examines criminological aspects of illegal migration, namely: factors, conditions provoking illegal migration, how much the number of crimes of this type is currently increasing, their number, causes and circumstances leading to the commission of this crime, as well as the category of persons who committed this type of crimes, conditions and circumstances of crimes committed by women, to commit a crime the commission of this crime increases from year to year, along with proposals and recommendations developed to combat illegal migration.